The relationship between attachment styles and autistic traits: considering the mediating role of empathy - Ameli, Samira; Ghaderi, Saber; Aslezaker, Maryam; DavazdahEmami, Mohammad Hassan; Dadashzadeh, Hossein (Researcher Bulletin of Medical Sciences, 2020)
Introduction: This purpose of this study is to investigate the relationship between autistic traits and attachment styles, and also the mediating role of empathy. Materials and Methods: 254 students of Tehran’s universities were chosen by using cluster-sampling method. After that, the demographic questionnaire, Close Relationship-Revised Questionnaire (ECR-R), Autism Spectrum Quotient–Short (AQ-S), and The Empathy Quotient-Short (EQ-S) forms were distributed amongst them in order to be filled. Results: Pearson product-moment correlation coefficient indicated that there is a significant relationship between the components of autistic traits with empathy, and avoidance and anxiety attachment. Also, there was a significant relationship between empathy and avoidance and anxiety attachment. Chi-square, SRMR, and other indexes indicate that empathy mediates the relationship between the autistic traits with the anxiety and avoidance attachment styles. Conclusion: According to the results, it can be concluded in the way that individuals with high autistic traits have lower empathy. Individuals, who report more anxiety and avoidance attachment, are less likely to have empathy in their relationships. As a final point, the high autistic traits are correlated with anxiety and avoidance attachment through their association with low empathy.